ANALISIS POTENSI KEWIRAUSAHAAN GULA AREN BADUI, AKSELERASI TEKNOLOGI INOVATIF DAN PEMBERDAYAAN SDM EKSIS DI MASA KRISIS DAMPAK COVID19 - Giovanni Inez Erika Margaretha; Geraldy Samuel Ivan; Roosganda Elizabeth; Rinsan Hutabarat; Annisaa Soeyono; Ratu Erlina G,; Didik Notosudjono; Arief T. Hardiyanto; Hamzah Bustomi; Hendro Sasongko; Martinus Tukiran; Hari Muharam (Universitas Galuh, 2023)
Changes in the business, economic, employment and income climate during the Covid 19 pandemic caused the global financial crisis to weaken economic growth, increase unemployment and people's purchasing power. This paper aims to present the various entrepreneurial potentials of Bedouin palm sugar, accelerate innovative technology and empower human resources for Bedouin palm sugar craftsmen to exist in the never-ending Covid-19 era. With the mixed method BEP, R/C ratio, SWOT which is interpreted descriptively qualitatively and reviews various research results and related literature. From the field findings it can be predicted that the high potential and entrepreneurial development that can be carried out by the Bedouin community in general. It is necessary to evaluate agricultural development policies from the institutional aspect of processed products, so that processed product strategies are not just raw materials and efforts to accurately formulate policies in supporting the increase in rural agro-industry going forward. Strategies for access to technology and information according to needs, the existence of adequate operational policy tools, the functioning of various supporting institutions (research, counseling, marketing), as well as regulatory support as government policies that are more focused and one-sided to accelerate the achievement of technological innovation.